Spatial Frequency Training Modulates Neural Face Processing: Learning Transfers from Low- to High-Level Visual Features - Peters, Judith C.; van den Boomen, Carlijn; Kemner, Chantal (Frontiers in Human Neuroscience, 2017)
Perception of visual stimuli improves with training, but improvements are specific for trained stimuli rendering the development of generic training programs challenging. It remains unknown to which extent training of low-level visual features transfers to high-level visual perception, and whether this is accompanied by neuroplastic changes. The current Event-Related Potential study showed that training-induced increased sensitivity to a low-level feature, namely low spatial frequency (LSF), alters neural processing of this feature in high-level visual stimuli. Specifically, neural activity related to face processing (N170), was decreased for low (trained) but not high (untrained) SF content in faces following LSF training. These novel results suggest that: 1) SF discrimination learning transfers from simple stimuli to complex objects and that 2) training the use of specific SF information affects neural processing of facial information. These findings may open up a new avenue to improve face recognition skills in individuals with atypical SF processing, such as in cataract or Autism Spectrum Disorder.